Effectiveness of providing the pemuda tangguh scholarship in the process of fulfilling learning needs at school to create high-achieving students - Tiara Aura Rizki; Dra. Susi Hardjati, M.AP (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract The “Beasiswa Pemuda Tangguh” (Resilient Youth Scholarship) program by the Surabaya City Government aims to provide fair access to education for high-achieving students—both academically and in extracurricular activities—as well as students from underprivileged families. The objective of this study is to analyze the effectiveness of the Beasiswa Pemuda Tangguh program in schools in fostering outstanding students. This study uses a descriptive method and a qualitative approach to collect data through observation. Based on several success factors, including goal achievement, socialization, program monitoring, and target accuracy, the research findings show that the program has been successful. It has effectively provided pocket money and school supplies to students, increased their motivation to study, and reduced the financial burden on families. Despite the program’s positive impact, issues such as students’ awareness of the need for regular digital reporting and reviewing efficiency remain concerns. Therefore, adjustments in guidance and supervision are needed to make the program more effective in producing a competitive and high-quality younger generation. Keywords: Program Effectiveness, Scholarship.